A ourivesaria no tempo de D. Afonso Henriques : proposta de uma revisão - Rosas, Lúcia (2013)
The expansion of the Romanesque architecture in Portugal coincides with the kingdom of D. Afonso Henriques (1143-1185). It was in this period that the Romanesque works on Lisbon's, Coimbra's, Oporto's and Braga Sees were initiated and the Monastery of the Holy Cross of Coimbra, was built, becoming the pantheon of the first kings of the 1st Dynasty. It is, however, extremely limited the number of objects of goldsmithing and other metals, dated with safety of Romanesque period, that arrived to our days. Through the reading and analysis of the publish documentation ((Livro Preto: Cartulário da Sé de Coimbra, Livro Santo de Santa Cruz. Cartulário do século XII e o Inventário do Tesouro da Sé de Viseu de 1188, among others) we try to identify the typologies and functions of gold, silver and other metals objects registered, donated or manufactured in the kingdom of D. Afonso Henriques.